Plan de MiPirámide para el consumo diario de alimentos y calorías - Glenda L. Warren; Claudia Peñuela (EDIS, 2010)
FCS8800Span, a 2-page illustrated fact sheet by Glenda L. Warren, is the Spanish language version of FCS8800/FY865 MyPyramid Plan for Daily Food and Calorie Intake. It provides tables for determining portion sizes of each food group by calorie levels, and calorie levels by age, gender, and activity level. Published by the UF Department of Family Youth and Community Sciences, August 2010.